(untitled) (Journal of Civil Engineering Researchers, 2026)
In reinforced concrete structures that are in corrosive environmental conditions, there is always a discussion of reinforcement corrosion. Therefore, because of the smaller diameter compared to longitudinal rebars and closer to the surface and consequently closer to the corrosive factors, stirrups are more affected by this corrosion. One of the most effective ways to prevent corrosion of stirrups is to use FRP rebars in structures exposed to corrosion. One of the disadvantages of using FRP rebar is that it is brittle, which makes it impossible to bend these rebars in a workshop environment. Therefore, a group of researchers suggested the use of straps made of FRP plates as stirrups and concluded some laboratory studies in this field. Now, the main goal of this study is to numerically investigate the behavior of beams made with this type of stirrups. For this purpose, 13 beams were modeled in Abaqus software and subjected to three-point bending loading. Also, things such as the type of FRP used, the width of the stirrups, the number of layers of the stirrups and the installation location of these stirrups were investigated and studied. The results of this study showed FRP stirrups with a cross-section equal to steel stirrups have a higher load capacity than beams with steel stirrups. Also, in terms of the beam’s ductility, the beam with FRP stirrups has less ductility than the beam with steel stirrups. Regarding the effect of the number of FRP stirrup layers, the results showed that in stirrups with fixed width and variable number of layers, increasing the number of FRP stirrup layers will increase the bearing capacity and reduce ductility.